A new and exact map of the dominions of the King of Great Britain on ye continent of North America : containing Newfoundland, New Scotland, New England, New York, New Jersey, Pensilvania, Maryland, Virginia and Carolina according to the newest and most exact observations. - Moll, Herman, d. 1732 (printed and sold by Tho. Bowles, 1715)
Map shows early eighteenth century major roads, major cities, forts, and Native American settlements near the southeastern coast of North America. Includes text about historical events. Insets: "The cataract of Niagara," "A draught of ye town and harbour of Charles-town," "A map of the principal part of North America," "A map of the improved part of Carolina with the settlements &c.," and [South part of Carolina and the east part of Florida]. Relief shown pictorially. Depths shown by soundings. Scale [ca. 1:3,000,000].